NEW COLONIZATION IN THE ISLAMIC WORLD - Muhibudin Muhibudin (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
In recent times, the dynamics of colonization have evolved beyond the conventional understanding of territorial conquests and dominations. This article delves into the phenomenon of